Penerapan Metode TOPSIS dalam Sistem Informasi Pengaduan Keresahan dan Kejahatan Lingkungan Bagi Masyarakat Berbasis Web (Studi Kasus: Kecamatan Ujungberung) - Neng Sri Lathifah Zulfa; Venny Aknestasya Alvianti; Dayanni Vera Versanika (LPPM STMIK Bandung, 2025)
Environmental conditions significantly affect community welfare and quality of life, making public participation in reporting environmental concerns and crimes essential. However, manual and unstructured reporting mechanisms often hinder timely and effective responses from authorities. This study aims to design and implement a web-based information system for environmental complaint management by integrating the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method. TOPSIS is applied to determine complaint handling priorities based on multiple criteria, including urgency, impact, frequency, and responsibility, using Euclidean distance calculations to positive and negative ideal solutions. The system is developed using the Laravel framework and MySQL database, and provides features such as user registration, complaint submission, status tracking, and complaint history. The results indicate that the proposed system effectively supports local authorities in objectively and systematically prioritizing complaint handling, while also improving efficiency, transparency, and responsiveness in environmental complaint management at the district level.